Model of Takaful in Malaysia - Adam, Khairunnisa; Karim, Norhayati; Parusali, Nurul Izzati; Bahauddin, Siti Nur Sabrina (2025)
Takaful is a Sharia system for managing risk transfer involving managers and participants (Iqbal, 2005). According to Ismail (2013), the principles of mutual assistance or al-ta'awun and sharing of responsibility are the basis for any transfer or sharing of risk in the Takaful system. In addition, the Takaful system does not take into account the elements of gharar which is defined as ambiguity, maisir, which is defined as gambling and riba in its risk management (Iqbal, 2005). In Malaysia, the takaful system has developed rapidly in line with the growth of the country's Islamic banking sector. Takaful has grown to become the main insurance option in Malaysia and around the world. This development shows that it is the best option for Islamic risk management. In Malaysia, both family Takaful and general Takaful products are used. Family Takaful products are designed to help participants and their family members when they are beset by misfortunes such as accidents, illnesses or diseases. It also has an annuity scheme but it does not include benefits paid through Individual Accident Takaful certificates. Bank Negara Malaysia (2012b) has stipulated that the concept of tabarru and the contract between the contributor and the takaful operator should be used for the basic contract in takaful products. This type of contract can consist of mudarabah, wakalah, a combination of mudarabah and wakalah and so on. The concept of tabarru can be used to achieve the main objective of Takaful which is to foster an attitude of cooperation, responsibility and protection of others who are facing hardship (Mustafa and Rahman, 2015). Aspects of Islamic philanthropy such as zakat and waqf are also associated with the term tabarru which means giving without return. This is due to the fact that the idea of Islamic philanthropy is one way to achieve the goals of society (Don et al., 2020).